Kebijakan Insentif Pajak Kendaraan Bermotor Selama Masa Pandemi Corona Virus Disease 2019 - Dhimam Zidny Siradj (Faculty of Law, Universitas Airlangga, 2021)
AbstractAs a result of the covid-19 pandemic, it has an impact on all sectors of human life in the world, which causes changes in human activities that cause various problems, one of which is in the economic field. In response to this, the government issued Regulation of the Minister of Finance Number 86 of 2020 concerning Tax Incentives for Taxpayers affected by the Covid-19 Pandemic. The East Java Provincial Government itself followed up with the issuance of the Governor of East Java Decree No. 188/394/KPT/013/2020 to become the implementing regulations. In this case, the East Java Provincial Government made a policy of exempting administrative sanctions on motorized vehicle taxes, free from transfer of motor vehicle names to deductions on motor vehicles during the Covid-19 pandemic.Keywords: Covid-19 pandemic; Tax Incentive Policy; Economy.AbstrakAkibat dari adanya pandemi covid-19 berdampak pada segala sektor kehidupan manusia di dunia yang menyebabkan perubahan aktivitas manusia yang menimbulkan berbagai masalah salah satunya adalah dalam bidang ekonomi. Untuk merespons hal ini pemerintah mengeluarkan Peraturan Menteri Keuangan Nomor 86 Tahun 2020 tentang Insentif Pajak Bagi Wajib pajak terdampak Pandemi Covid-19. Pemerintah Provinsi Jawa Timur sendiri menindaklanjuti dengan dikeluarkanya Keputusan Gubernur Jawa Timur No. 188/394/KPT/013/2020 guna menjadi aturan pelaksanaanya. Dalam hal ini Pemerintah Provinsi Jawa Timur membuat kebijakan membebaskan Sanksi Administratif pajak kendaraan bermotor, bebas bea balik nama kendaraan bermotor hingga potongan pokok pajak pada kendaraan bermotor dalam masa pandemi covid-19. Kata Kunci: Pandemi Covid-19; Kebijakan Insentif Pajak; Ekonomi.